MONITORING OF AIR POLLUTION IN UZBEKISTAN (American Journal of Pedagogical and Educational Research, 2023)
The article presents the results of the analysis of data on air pollution in the cities of the Republic of Uzbekistan (RUz) in 2021 based on the reporting data of the Service for Monitoring Air Pollution, Surface Water and Soil of the Center for Hydrometeorological Service of the Republic of Uzbekistan. Analyzed data on the study of the concentration of the main pollutants: dust, sulfur dioxide, carbon monoxide, nitrogen dioxide and oxide, ozone, as well as specific impurities and heavy metals. The results showed that the average annual concentrations of all pollutants under consideration did not exceed the maximum allowable concentrations, only in the atmospheric air of some cities was an excess of the average daily maximum allowable concentrations (MPC) observed. Pollution index. The atmospheric air pollution index (API) in the cities was in the range of 1.38-4.85.